A common European Curriculum for Dental Hygiene ‐ Domain II: Safe and Effective Clinical Practice. (19th September 2020) - Öhrn, Kerstin; van Boxtel, Agnes; Field, James
Abstract: This position paper outlines the areas of competence and learning outcomes of the Common European Curriculum for Dental Hygiene (CECDH) that specifically relate to Safe and Effective Clinical Practice. Dental hygienists are required to ensure that they are capable of providing safe and appropriate care for their patients, whilst operating effectively within a wider team. The care provided should be based on contemporaneous evidence wherever possible, and the quality of care and the management systems that underpin it should be regularly audited and improved.